Relasi Allah dalam Panggilan Yesaya: Studi Kata ’ăḏōnāy, kissê, dan YHWH ṣəḇā’ōwṯ Berdasarkan Yesaya 6:1-13 - Farel Yosua Sualang; Samgar Setia Budhi (Integritas: Jurnal Teologi, 2022)
Book of Isaiah has many uses of figurative language styles (such as: metaphor, simile, metonymy, etc.), including the call of Isaiah (6:1-13). This article is unique in its interpretation of the study of the words “’ăḏōnāy,” “kissê,” and “YHWH ṣəḇā’ōwṯ” by paying attention to the overall structure of Isaiah 6:1-13. As a result, by using sub-hermeneutic qualitative studies, especially word-study, this article finds two synthesizing combinations of the emphasis on the meaning of the “’ăḏōnāy,” “kissê,” and “YHWH ṣəḇā’ōwṯ” in the structure of Isaiah 6:1-13 . First, the words “’ăḏōnāy,” “kissê,” and “YHWH ṣəḇā’ōwṯ” show God's power over his creation and attach importance to His dignity as king. second, the words above focus on the relationship between God and humans (Isaiah, Israel) who worship and serve Him as God who has authority over His creation.